Analysis Of The Utilization Of Regional Property Leases In Increasing Regional Original Income In Bulukumba Regency - Suci Rahma Sari; Mediaty Mediaty; Nur Dwiana Sari Saudi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the level of effectiveness of the use of rental of regional property (BMD) in increasing the original regional income (PAD) of Bulukumba Regency, to analyze the level of efficiency of the use of rental of regional property (BMD) in increasing the district's original income (PAD). Bulukumba, To Analyze the Economic Level of Utilization of Regional Property Rentals (BMD) in Increasing Original Regional Income (PAD) of Bulukumba Regency. This research uses a descriptive quantitative approach. The type of money data used is secondary data in Bulukumba Regency. The data used in this research are Regional Property Rentals (BMD) and Regional Original Income (PAD). The data analysis technique uses quantitative descriptive using the financial ratio formula: Effectiveness and Efficiency Ratios and economic Ratios. The results of the analysis show that the Bulukumba Regency area is seen from (1) the average Effectiveness Ratio of 37.29 percent, it can be said that the utilization of rental property belonging to the Bulukumba Regency area is not effective (2) the Efficiency Ratio, the average of which is 287 percent, then it can be said that renting regionally owned trunks in Bulukumba district is not efficient. 3) The Economic Ratio is 83.29 percent, so it can be said that renting regionally owned trunks in Bulukumba district is quite economical.